Pengaruh Keselamatan Kerja, Kesehatan Kerja, dan Work Life Balance terhadap Produktivitas Kerja Karyawan CV. Saprotan Utama Semarang - Lamhalahera Prabandiandra; Noventia Karina Putri; Hawik Ervina Indiworo (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to determine the influence of occupational safety, occupational health, and work-life balance on the work productivity of employees of CV. Saprotan Utama Semarang. This study uses a quantitative method with a survey research type. Sampling was carried out using the probability sampling method with the number of respondents studied as many as 180 employees. The data collection process was carried out by distributing questionnaires directly to the performance of CV. Saprotan Utama Semarang employees. This study uses IBM SPSS 26 software with multiple regression tests as a hypothesis testing method. The results of the analysis and discussion show that the variables have a positive and significant influence between Occupational Safety, Occupational Health, and Work-life Balance on employee work productivity. The results of the analysis show that the Occupational Safety variable has a significant positive effect on employee work productivity with a significance value of 0.37, Occupational Health has a significant positive effect on employee work productivity with a significance value of 0.009, and Work-life Balance has a significant positive effect on employee work productivity with a significance value of 0.000.